2021
DOI: 10.34128/jtai.v8i2.144
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Oil Losses Pada Proses Pengolahan Minyak Inti Kelapa Sawit Di Pt. Xyz Dengan Metode Seven Tools

Abstract: One form of efficiency that can be done by palm oil mill companies so that production targets are achieved is to reduce the number of oil losses or loss of oil in the process of making their products, in this case, are CPO and PKO. This is because the lower the amount of oil losses, the higher the CPO and PKO that will be produced. This study aims to analyze oil losses in the processing of Palm Kernel Oil or PKO with the seven tools method. Data collection techniques in this study used case studies based on li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
2
0
5
Order By: Relevance
“…Many factors were thought to have contributed to this case, such as minor damage to the pressing unit and the high oil levels in the Palm Kernel Expeller. However, if referred to several studies, it was found that the percentage of oil loss in the pressing unit was < 8% [19,27]. Hence, based on this standard, the percentage of oil loss remained within the normal limits.…”
Section: Determination Of Oil Loss In Mealmentioning
confidence: 93%
See 1 more Smart Citation
“…Many factors were thought to have contributed to this case, such as minor damage to the pressing unit and the high oil levels in the Palm Kernel Expeller. However, if referred to several studies, it was found that the percentage of oil loss in the pressing unit was < 8% [19,27]. Hence, based on this standard, the percentage of oil loss remained within the normal limits.…”
Section: Determination Of Oil Loss In Mealmentioning
confidence: 93%
“…The investigation of oil loss in CPKO processing at PT XYZ was carried out using the seven tools method, which focuses on case studies (library studies) and direct field studies. The results of the qualitative descriptive study concluded that the company suffered losses due to high oil losses for four months of 8.92% [19]. In addition to CPKO, oil loss is also occurred in CPO, which was analyzed using statistical process control methods at PT Bastian Olah Sawit Tungkal Palembang.…”
Section: Introductionmentioning
confidence: 99%
“…Metode deskriptif kualitatif dengan memaparkan dan menganalisa data hasil temuan yang didapat di lapangan, menganalisa data berupa temuan yang mudah dipelajari, diteliti, sistematis, logis, dan menemukan penyebab timbulnya masalah (Ulimaz et al, 2021).…”
Section: Metode Penelitianunclassified
“…Proses produksi dikatakan baik apabila proses tersebut menghasilkan produk yang memenuhi standar yang telah ditetapkan (Adianti, 2019). Pengolahan atau produksi minyak kelapa sawit yang baik merupakan salah satu faktor yang menentukan keberhasilan usaha perkebunan kelapa sawit (Ulimaz, 2021).…”
Section: Pendahuluanunclassified